Consumers' knowledge and use of nutritional information on food labels - Ana Carolina Bail Morais; Lize Stangarlin-Fiori; Renata Labronici Bertin; Caroline Opolski Medeiros (Universidade do Estado do Rio de Janeiro, 2020)
Food labelling is important to communication between food producers and consumers. For consumers to have greater autonomy in terms of their food choices, it is important to facilitate a correct interpretation about what is on a food label. This paper assessed consumers' knowledge and use of nutritional information on food labels. Cross-sectional exploratory quantitative, "blind" research carried out in 2018 in a public university in Brazil, with 415 consumers aged 18 years or older. A structured questionnaire with a score ranging from 0 to 24 was applied. Descriptive analysis, Spearman correlation coefficient, the Kruskal-Wallis test and the Mann Whitney test were employed. Participants were individuals aged 21.02 ± 2.89 years, of which 58.31% were female. Many consumers reported they read food labels frequently (56.39%). The mean score was 14.99 ± 4.12. The knowledge score mean was affected by age (p = 0.039) and income (p = 0.020). Participants who used nutritional claims as a criterion for purchase (p = 0.004) had higher scores. The biggest issues in interpreting nutritional labels were related to mandatory nutrient claims and the terms "trans-fat free (0%)", "functional food", "diet" and "light". Food label regulation is a process currently under review in Brazil, so research on the use and knowledge of nutritional information on food labels by young adult consumers becomes important. It will contribute to the discussion of the revision of legislation, as well as helping professionals guide consumers in the interpretation of labels.